AS „OLAINFARM” SEWAGE TREATMENT PLANT EFFICIENCY IMPROVEMENT - Grisone, Agnese; Teirumnieks, Edmunds (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2017)
Researched the problem is that during the manufacturing process mother liquor is fed to the sewers. Then the mother liquors into the biological treatment plant. Results and evaluation are reflected in the input and output samples of waste water results in which the sample results are not following the requirements laid down. Wastewater treatment plants have been built a long time ago and need to supplement existing equipment to clean up the quality of untreated wastewater.